An assessment of earthquake vulnerability in a low income settlement in Delhi, India - Kishore, Kamal; Sheng, Yap Kioe; Hollister, David; Wickramanayake, B.W.E.; Sida (Swedish International Development Co-operation Agency) (Bangkok : Asian Institute of Technology, 1996)
This century has witnessed an exponential rise in losses due to natural disasters. The patterns indicate that the causes lie beyond just the geophysical processes. There is an ever-growing need to look at disaster vulnerability of communities in not only physical terms but also in social, organizational and attitudinal realms. Although a lot has been written in terms of conceptual frameworks, there is a dearth of practicable tools for assessing the vulnerability of communities. This study sets out to put together a tentative methodology, for assessing earthquake vulnerability, based on earlier works and expert advice. Subsequently, this methodology is applied in a specific context. The study takes up the case of Delhi, a rapidly growing megacity in India. A low income settlement of a population of about fifty thousand is chosen. In terms of its housing stock the study area is representative of more than a third of Delhi's houses. The probable physical damage, for earthquakes of two different intensities, and corresp onding casualty patterns are estimated . The study quantifies the direct economic losses and deals with the indirect losses qualitatively. It also touches upon the probable impact in social and organizational domains. Four different scenarios are generated: one, the existing scenario; two, a hypothetical scen ario for the year 1996 wherein it is assumed that the entire housing stock incorporates some basic elements of earthquake resistant construction; three, a future scenario for the year 2014 based on existing trends; and four, an alternative scenario for 2014 wherein some tangible interventions are made from 1996 onwards. The study compares these four scenarios and draws recommendations for earthquake mitigation and preparedness in the study area. ·At another level, the study discusses the larger methodological issues relating to vulnerability analysis -- its utility and the gaps in the existing state of the art methodologies.
Thesis (M. Sc.) - Asian Institute of Technology, 1996
A thesis submitted in partial fulfilment of the requirements for the degree of Master of Science
Keywords: Earthquake hazard analysis -- India -- Delhi